Synthesis and Characterization of BiVO4/S,N-CQDs as Photoelectrochemical Water Splitting Material - Arthaningtyas, Herlina; Sambudi, Nonni Soraya; Roza, Liszulfah; Fauzia, Vivi; Sufian, Suriati; Pradanawati, Sylvia Ayu; Buys, Yose Fachmi; Vikaliana, Resista (Applied Science and Engineering Progress, 2025)
Hydrogen has emerged as a promising renewable energy source to replace fossil fuels, driving the need for efficient and low-emission hydrogen production methods. Among these, photoelectrochemical (PEC) water splitting using solar energy and semiconducting materials as photoanodes holds significant potential. This study focuses on enhancing the performance of bismuth vanadate (BiVO4), a highly promising photoanode material, synthesized on fluorine-doped tin oxide (FTO) substrates via a hydrothermal method. This research aims to improve the efficiency and stability of BiVO4 as a photoelectrochemical anode material by integrating sulfur-nitrogen-doped carbon quantum dots (S,N-CQDs), derived from Egeria densa algae, to minimize charge recombination and enhance light absorption as well as the efficiency of solar energy conversion to hydrogen. To address the challenge of charge recombination, S,N-CQDs were integrated into BiVO4 using a spray-coating method in varying volumes (0, 2.5, 5, 7.5, and 10 mL). The incorporation of S,N-CQDs significantly reduced the band gap of BiVO4, with the most notable reduction at 7.5 mL (from 3.14 eV to 2.70 eV). This modification resulted in enhanced PEC water splitting performance, with a maximum photocurrent density of 0.0698 mA/cm² and a photoconversion efficiency of 0.0131%. Additionally, the optimized BiVO4/S,N-CQDs photoanode exhibited a double-layer capacitance (Cdl) of 0.102 mF/cm², indicating improved charge transport properties. These results demonstrate that the integration of S,N-CQDs into BiVO4 not only enhances PEC efficiency but also contributes to the development of cost-effective, sustainable solutions for solar-driven hydrogen production, supporting the transition to a renewable energy future.